Student perceptions of online statistics and mathematics learning: A multi-dimensional analysis based on feedback - Elkahlout, Gamal R. (Edelweiss Applied Science and Technology, 2025)
This study investigates the factors that influence students' perceptions of online learning in statistics and mathematics courses. Using a 28-item survey with a 4-point Likert scale (Cronbach's alpha = 0.9), we analysed seven dimensions of the online learning experience: course textbooks, virtual and physical classes, Learning Management System, utilization, teaching materials, recorded YouTube lectures, PPT, and the role of English as the language of instruction. Key findings reveal that 62% of students are satisfied with virtual classes, 84% prefer YouTube lectures over pre-recorded sessions, and 90% find PPTs helpful. Hypothesis testing (using t-tests and ANOVA) revealed significant differences in student perceptions regarding gender, GPA, university branch, specialization, enrolled course, and employment status. Employed students showed a preference for virtual classes over physical classes and greater confidence in their English language skills. Based on these findings, we recommend improving assessment feedback, enhancing English language support, and strategically using visual aids, particularly in mathematics courses.